Determination of Indoor Radon Concentration in Thi Qar Province Houses by using CR-39 SSNTD - Rashid, Jabbar M. (University of Thi-Qar Journal of Science, 2014)
The possible detrimental health effects of the inhaled radon and its decay products are in the limelight of interest of professionals as well as of the public. In the present work the passive integrated dosimeter technique with solid state nuclear track detectors (SSNTDs) super grade CR-39, was used to measure the concentration of the radioactive radon gas (Rn-222) indoor for 12 different locations in Thi Qar province. 176 detectors ( 1.0 cm x 1.0 cm x 0.5 cm) were prepared and were distributed in the chosen locations , after 90 days ( November, December 2012 and January 2013) the detectors were collected and treated chemically using etching conditions which controlled by four principals variables ( etching solutions ,temperature , morality and etching time). The tracks per unit area in each detector were determined by using MICROS Crocus II MCX100LCD optical microscope. Results obtained showed that radon average concentration indoors was varies from 25.66 Bq/m3 in Bateha to 113.63 Bq/m3 in Fuhood, and the annual effective dose according to these concentrations are 0.890 mSv/y and 3.941mSv/y respectively. Results indicate that the houses surveyed had indoor radon levels within permissible level when ICRP1993 recommended limit of 600 Bqm-3 was used. Few houses had higher radon levels if NRPB (Health Protection agency) UK and US (environmental protection agency) EPA limits of 200 and 148 Bq m-3 were used. The overall average for the concentrations of radon in indoor air in the province of Thi Qar in this study is 66.989 Bq/m3 .